2017
DOI: 10.3354/dao03141
|View full text |Cite
|
Sign up to set email alerts
|

Oral neoplasms in pickhandle barracuda Sphyraena jello from India

Abstract: We report the spontaneous occurrence of oral neoplasms in pickhandle barracuda Sphyraena jello Cuvier, 1829 from Parangipettai, on the southeast coast of India. A total of 11736 fish were examined, of which 43 were affected with oral tumours, with an overall prevalence of 0.37%. Gross and clinical symptoms included reddish to grayish-white distended tumourous growths on the gingiva, intra-oral bones and tongue. The tumours exhibited delayed eruption and intra-or extra-oral swelling, varied in consistency from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Psammomatoid ossifying fibroma is a rare tumour in fish. The anal (case 1) lesion observed in seabream resembles tumours in pickhandle barracuda, Sphyraena jello (Singaravel et al., ) in which osteoid fibroma with atypical ossification was observed. Nodular fasciitis is a benign, reactive proliferation of fibroblasts in the subcutaneous tissues and deep fascia.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Psammomatoid ossifying fibroma is a rare tumour in fish. The anal (case 1) lesion observed in seabream resembles tumours in pickhandle barracuda, Sphyraena jello (Singaravel et al., ) in which osteoid fibroma with atypical ossification was observed. Nodular fasciitis is a benign, reactive proliferation of fibroblasts in the subcutaneous tissues and deep fascia.…”
mentioning
confidence: 95%
“…Recently, however, we have reported a high incidence of tumours in both cultured and captured fish in India, such as Mugil cephalus (Jithendran, Natarajan, Pramoda, & Thiagarajan, ; Singaravel, Gopalakrishnan, Raja, Vijayakumar, & Asrafuzzaman, ), Sardinella longiceps (Gopalakrishnan et al., ; Sinduja, Vijayakumar, & Gopalakrishnan, ; Singaravel et al. , ; Singaravel, Gopalakrishnan, Vijayakumar, Raja, & Asrafuzzaman, ,b), Sphyraena barracuda (Gopalakrishnan et al., ), Chanos chanos (Ananda Raja, Panigrahi, & Kumar, ), Puntius sarana (Sahoo, Mohanty, Das, Mahapatra, & Saha, ), Sphyraena jello (Singaravel, Gopalakrishnan, Raja, Vijayakumar, & Asrafuzzaman, ,b; Vijayakumar, Gopalakrishnan, Raja, & Sinduja, ), Lates calcarifer (Vijayakumar, Raja, Singaravel, & Gopalakrishnan, ), Arius jella (Singaravel, Gopalakrishnan, Vijayakumar, & Raja, ) and Rastrelliger kanagurta (Singaravel, Gopalakrishnan, & Raja, ). Tumours in goldlined seabream ( R. sarba ) have not previously been seen, and to our knowledge, this is the first such report.…”
mentioning
confidence: 99%
“…Furthermore, the usefulness of fish as a model for studying human diseases including neoplasms has also prompted researchers to pay much interest in unravelling tumorigenesis in fish (Schmale, Nairn, & Winn, 2007). While there are no systematic studies on fish neoplasms from India, some of the reported tumours include odontoma in pickhandle barracuda, Sphyraena jello (Singaravel et al, 2017), cutaneous myxoma in blackfin sea catfish (Singaravel, Gopalakrishnan, Vijayakumar, & Raja, 2015), and lipoma in a gold fish (Sood et al, 2017). Fibromas are benign neoplasms of mesenchymal origin composed of fibrous connective tissue.…”
Section: Introductionmentioning
confidence: 99%